Persistence Study of Thiamethoxam and Its Metabolite in Kiwifruit for Establishment of Import Tolerance - Cho, Il Kyu; Lee, Gyeong Hwan; Cho, Woo Young; Jeong, Yun-Su; Kim, Danbi; Kim, Kil Yong; Hyoung, Gi-Woo; Kim, Chul Hong (Hanguk hwangyeong nonghak hoeji, 2022)
BACKGROUND: Pre-harvest interval and decline pattern of thiamethoxam were determined in kiwifruit using liquid chromatography-tandem mass spectrometry (LCMS/MS). The study was carried out to propose import tolerance using OECD maximum residue limit (MRL) calculator for the export promotion of kiwifruit to Taiwan. METHODS AND RESULTS: The thiamethoxam residue in kiwifruit was determined by using the LC-TriQ-MS/ MS with the analytical process to set up the import tolerance under greenhouse conditions for Taiwan. Excellent linearity was observed for all of the analytes with a determination coefficient (R2 )≥0.99. The limit of quantification was determined to be 0.01 mg/kg for both thiamethoxam and clothianidin in kiwifruit. Linearity was determined from the co-efficient of determinants (R2 ) obtained from the seven-point calibration curve. The standard calibration curve showed as follows; 1) Site 1 (Gimje): y = 944,406X + 1,583 (R2 =0.9995), 2) Site 2 (Goheung): y = 1,356,205X + 934 (R2 =0.9983), and 3) Site 3 (Jangheung): y = 1,239,937X – 3,090 (R2 =0.9908). The residue of thiamethoxam in the kiwifruit for three decline trials showed the range of 0.35 to 0.56 mg/kg in site 1 (Gimje), 0.24 to 0.55 mg/kg in site 2 (Goheung), and 0.28 to 0.42 mg/kg in site 3 (Jangheung), respectively. However, clothianidin was not detected in all of the treatments. The maximum residual amounts (decline) in the samples, sprayed according to the safe-use standard for thiamethoxam 10% WG in kiwifruit (30 days before harvest, 3 sprays every 7 days) were 0.56 mg/kg in site 1, 0.55 mg/kg in site 2, and 0.42 mg/kg in site 3, respectively. CONCLUSION(S): The import tolerance (IT) of thiamethoxam for kiwifruit may be proposed to be 0.9 mg/kg by using the OECD MRL calculator. KCI Citation Count: 0